LAGU MODEL UNTUK ANAK SEKOLAH DASAR DALAM MENGEMBANGKAN DAYA MUSIKALITAS - Rini Dias; Syahrel Syahrel; Syeilendra Syeilendra (SENDRATASIK UNP, 2012)
This research purpose to for describe the learning methods used in vocal training to students in the selection of songs child model for the development of musicality. This study used descriptive qualitative research methods. Religious studies is the SDN 31 Tj Aur Padang. The results showed that the selection of songs is the song Kampuang child model Nan Jauah dimato and rainbow-rainbow song can enhance the musicality of students because of the rhythm, melody and expression of the song that contains the meaning of positive and good for the psychological development of children and the methods used in cultural arts and skills learning is a method of lecture, discussion, and demonstration.Keyword: Song child model, qualitative, descriptive, rhythm, melody, expression